Software architecture : 14th European Conference, ECSA 2020, L'Aquila, Italy, September 14-18, 2020, Proceedings /: 14th European Conference, ECSA 2020, L'Aquila, Italy, September 14-18, 2020, Proceedings. (2020) - Unknown
No abstract available